Classifying Cam Morphology by the Alpha Angle: A Systematic Review on Threshold Values. Issue 8 (7th August 2020) - van Klij, Pim; Reiman, Michael P.; Waarsing, Jan H.; Reijman, Max; Bramer, Wichor M.; Verhaar, Jan A.N.; Agricola, Rintje
Background: The alpha angle is the most often used measure to classify cam morphology. There is currently no agreement on which alpha angle threshold value to use. Purpose: To systematically investigate the different alpha angle threshold values used for defining cam morphology in studies aiming to identify this threshold and to determine whether data are consistent enough to suggest an alpha angle threshold to classify cam morphology. Study Design: Systematic review; Level of evidence, 3. Methods: The Embase, Medline (Ovid), Web of Science, Cochrane Central, and Google Scholar databases were searched from database inception to February 28, 2019. Studies aiming at identifying an alpha angle threshold to classify cam morphology were eligible for inclusion. Results: We included 4 case-control studies, 10 cohort studies, and 1 finite-element study from 2437 identified publications. Studies (n = 3) using receiver operating characteristic (ROC) curve analysis to distinguish asymptomatic people from patients with femoroacetabular impingement syndrome consistently observed alpha angle thresholds between 57° and 60°. A 60° threshold was also found to best discriminate between hips with and without cam morphology in a large cohort study based on a bimodal distribution of the alpha angle. Studies (n = 8) using the upper limit of the 95% reference interval as threshold proposed a wide overall threshold range between 58° and 93°. When stratified by sex, thresholds between 63° and 93° in male patients and between 58° and 94° in female patients were reported. Conclusion: Based on the available evidence, mostly based on studies using ROC curve analysis, an alpha angle threshold of ≥60° is currently the most appropriate to classify cam morphology. Further research is required to fully validate this threshold.